82 The 'Boston Six' and the Pilgrim. (22nd November 2019) - Hunt, Paul; Warren, Alison
Abstract : Throughout the United Kingdom, NHS Trusts are faced with a shortage of qualified Nurses as well as on-going recruitment problems. In some areas, the resultant effect of the workforce deficit has led to a lack of specialist staff trained in specific branches of Nursing and Medicine, which in turn has had an impact on the quality of care delivered. One NHS Trust in particular reached a critical point with the delivery of Urgent and Emergency Paediatric Care, and was critically short of Paediatric skills in this area. In December 2018, Health Education England, NHS England and NHS Improvement sent a request to the Chief Executives and Directors of Nursing of eight NHS Trusts to release senior non-medical paediatric educators from their organisations to form part of a 'Strike Force'. The aim was to work alongside the Emergency Department staff to promote the safe care of infants, children and young people, following two 'Inadequate' Care Quality Commission (CQC) ratings. This was an unprecedented move by Health Education England. Five NHS Trusts from around the country agreed to release six staff in total, on a three month secondment. The objective was to support the 'bedside' care delivery with their clinical expertise and to formulate a robust and sustainable educational programme within the Emergency Department in order to change the culture surrounding the care of the sick child. This presentation describes the innovative approach that Health Education England adopted, the challenges that were faced by the Health Education England Fellows and how some of these challenges were overcome in a failing establishment.